Green synthesis of silver nanoparticles on biosilica diatomite: Well-dispersed particle formation and reusability. (February 2023) - Min, Ki Ha; Shin, Jin Woo; Ki, Mi-Ran; Pack, Seung Pil
Abstract: Silver nanoparticles (AgNPs) are obtained herein by green synthesis using plant extracts instead of chemical reagents. However, the AgNPs fabricated via green synthesis are prone to aggregation, and their reproducible formations are difficult owing to the lack of capping ability in the extract. Although such aggregations of AgNPs are also observed in chemical synthesis, the phenomenon is more severe in green synthesis. In this study, we used Pinus koraiensis pinecone extract as a new green-synthetic agent along with 1 mM AgNO3 and diatomite (DE) as the biosilica surface to prepare AgNPs stably. Scanning electron microscopy with energy-dispersive X-ray spectroscopy analysis confirmed that the AgNPs were formed on DE by green synthesis with a size of 27 nm; they were non-aggregated and well-dispersed on the DE surface. The AgNP-coated DE composite (AgNPs/DE) showed antibacterial activity that could kill > 99% of E. coli and S. aureus within one hour. Further, the AgNPs/DE with antimicrobial activity can be used up to five times repeatedly. The use of DE in the green synthesis of nanoparticles can thus provide advantages such as adequate dispersion and enhanced ability of the AgNPs. The results obtained herein support the environmentally friendly strategy of preparation and application of AgNPs. Graphical Abstract: ga1 Highlight: Green synthesis of silica nanoparticle (AgNPs) by pinecone extract was done on diatomite (DE) to yield DE/AgNPs. In AgNPs/DE composite, the formed AgNPs are well dispersed on diatomite surface. AgNPs/DE composite showed good antibacterial activity for gram-positive and gram–negative bacteria. Antibacterial activity of AgNP can be re-used via AgNPs/DE composite.